Statistical method of assigning fiducial limits to a protective effect estimated from biological assays which compare three groups of results - Simionovici, M.; Molnar, I. A.; Bonciocat, N. (Cercetări Marine - Recherches Marines, 2026)
A statistical method of assigning fiducial limits to a protective effect is proposed. The method is based on a theorem of mathematical statistics given by Fieller and may be applied to all experimental procedures which measure an adequate quantitative response in three groups of animals: intoxicated animals, intoxicated and treated animals, and control animals. A numerical example of assigning fiducial limits to the antilipidical effect of the mucopolysaccharide extracted from Mytilus galloprovincialis in the intoxication with Triton, is also given.